Single-Domain Antibodies and the Promise of Modular Targeting in Cancer Imaging and Treatment - Iezzi, María Elena; Policastro, Lucía; Werbajh, Santiago; Podhajcer, Osvaldo; Canziani, Gabriela Alicia (Frontiers in Immunology, 2018)
Monoclonal antibodies (mAbs) and their fragments have significantly changed the outcome of cancer in the clinic, effectively inhibiting tumor cell proliferation, triggering antibody-dependent immune effector cell activation and complement mediated cell death. Along with a continued expansion in number, diversity and complexity of validated tumor targets there is an increasing focus on engineering recombinant antibody fragments for lead development. Single domain antibodies (sdAbs), in particular those engineered from the variable heavy chain fragment (VHH gene) found in Camelidae heavy chain antibodies (HcAbs or IgG2 and IgG3), are the smallest fragments that retain the full antigen-binding capacity of the antibody with advantageous properties as drugs. For similar reasons, growing attention is being paid to the yet smaller variable heavy chain new antigen receptor (VNAR) fragments found in Squalidae. SdAbs have been selected, mostly from immune VHH libraries, to inhibit or modulate enzyme activity, bind soluble factors, internalize cell membrane receptors or block cytoplasmic targets. This succinct review is a compilation of recent data documenting the application of engineered, recombinant sdAb in the clinic as epitope recognition ‘modules’ to build monomeric, dimeric and multimeric ligands that target, tag and stall solid tumor growth in vivo. Size, affinity, specificity and the development profile of sdAbs drugs are seemingly consistent with desirable clinical efficacy and safety requirements. But the hepatotoxicity of the tetrameric anti-DR5-VHH drug in patients with pre-existing anti-drug antibodies halted the phase I clinical trial calls for the pre-screening of immune and poly-specific reactivity of sdAb leads.